Detection of different categories of hepatitis B virus (HBV) infection in a multi‐regional study comparing the clinical sensitivity of hepatitis B surface antigen and HBV‐DNA testing. Issue 1 (27th September 2016) - Lelie, Nico; Bruhn, Roberta; Busch, Michael; Vermeulen, Marion; Tsoi, Wai‐Chiu; Kleinman, Steven; ,
Abstract : BACKGROUND: Twenty‐two users of individual donation nucleic acid amplification technology (ID‐NAT) in six geographical regions provided detailed hepatitis B virus (HBV) infection data in first‐time, lapsed, and repeat donations and classified confirmed HBV‐positive donors into different infection categories. These data were used to compare the clinical sensitivity of hepatitis B surface antigen (HBsAg) and HBV‐DNA testing. STUDY DESIGN AND METHODS: In total 10, 981, 776 donations from South Africa, Egypt, the Mediterranean, North and Central Europe, South East Asia, and Oceania were screened for HBV‐DNA using the Ultrio assay (Grifols/Hologic) and for HBsAg using a chemiluminescence immunoassay, and 9455 HBV‐infected donations were identified. HBsAg‐negative window period (WP), HBsAg‐positive and occult HBV infection (OBI) stages were determined using supplemental serology, quantitative polymerase chain reaction, and replicate multiplex and discriminatory HBV NAT test strategies. For two regions, additional data sets using the more sensitive Ultrio Plus assay were assessed. RESULTS: Regional HBV detection rates in first‐time donors varied between 0.08% and 1.07%, with WP NAT yield rates varying between 1:7700 and 1:294, 000 and OBI NAT yield rates varying from 1:3900 to 1:59, 000. HBsAg CLIA detected 97.0% of infections in first‐time donors, 62.7% in lapsed donors, and 41.0% in repeat donors; whereas Ultrio detected 93.1%, 95.0%, and 98.3% of infections in these respective groups. HBV‐DNA detection rates in HBsAg‐positive donors varied from 90.2% to 96.3% between regions but increased significantly (range, 95.2‐98.2%) with the Ultrio Plus assay. CONCLUSION: ID‐NAT and serology are complementary in detecting HBV infection in first‐time donors, but HBV‐DNA is superior to HBsAg detection in repeat donors.